Fragility of Safe Asset Markets - Eisenbach, Thomas M; Phelan, Gregory (Review of Financial Studies, 2026)
Abstract In March 2020, safe asset markets experienced surprising and unprecedented price crashes. We explain how strategic investor behavior can create such market fragility in a model with investors valuing safety, investors valuing liquidity, and constrained dealers. While safety investors and liquidity investors can form a symbiotic relationship with offsetting trades during times of stress, strategic interactions among liquidity investors harbor the potential for self-fulfilling fragility. When the market is fragile, standard flight-to-safety can have a destabilizing effect and trigger a “dash-for-cash” by liquidity investors. Well-designed policy interventions can reduce market fragility ex ante and restore orderly functioning ex post.